2022
DOI: 10.3390/molecules27134165
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating between Parallel, Anti-Parallel and Hybrid G-Quadruplexes: Mechanistic Details on Their Binding to Small Molecules

Abstract: G-quadruplexes (G4) are now extensively recognised as a peculiar non-canonical DNA geometry that plays a prime importance role in processes of biological relevance whose number is increasing continuously. The same is true for the less-studied RNA G4 counterpart. G4s are stable structures; however, their geometrical parameters may be finely tuned not only by the presence of particular sequences of nucleotides but also by the salt content of the medium or by a small molecule that may act as a peculiar topology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…This aspect may warrant interest. It is known that the binding features are the complicate superimposition of interactions between tetrads and loops, whose relative strength comes from small details in both host and guest structures; on the other hand, these loop interactions are those which may determine selective binding to a peculiar sequence of biomedical interest [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect may warrant interest. It is known that the binding features are the complicate superimposition of interactions between tetrads and loops, whose relative strength comes from small details in both host and guest structures; on the other hand, these loop interactions are those which may determine selective binding to a peculiar sequence of biomedical interest [26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent analyses of the interaction between extended condensed aromatic species and different G4 motifs showed that binding modes other than the "sitting-atop" mode may also be at play [24,25]. However, a rational drug design process to develop molecules with different affinity towards different quadruplexes, or with improved binding ability towards a given quadruplex sequence, is still difficult [26]. G4s are difficult targets because of the following: (i) the main interaction often involves stacking with the external guanine quartets, and this structural motif is always present, regardless of the type of sequence and assumed folding; and (ii) despite the considerable interest in this research sector, the number of structures obtained is still limited, especially when compared with the very high number of identified Putative Quadruplex Sequence (PQSs-estimated ca.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ]). In addition, different structures show variable affinity towards G-quadruplex-binding proteins [ 52 , 53 ] and small molecules [ 54 , 55 , 56 ], and this can be the basis for the selection of molecules that are specific for different structures. Given the abundance of polymorphic G-quadruplex structures, it is thus tempting to assert that cells can discriminate between different G4 topologies, which would then be linked to distinct biological roles in live cells [ 19 ], although the extent to which this is true is yet to be elucidated.…”
Section: Overview Of the G-quadruplexmentioning
confidence: 99%
“…In this protein probe, two identical G4-binding domains (23-amino acid residues each) are connected with linker peptide to bind G-quadruplexes with sufficient strength. Small molecular ligands, which distinguish different conformations of G-quadruplexes each other, were also reported [ 65 , 66 , 67 ].…”
Section: Dna G-quadruplexes In Human Telomerementioning
confidence: 99%